Coil occlusion of aberrant arteries to pulmonary sequestration in a case with pulmonary atresia with intact ventricular septum: successful treatment of repetitive myocardial ischaemic attacks. (5th October 2016) - Ono, Akemi; Hayabuchi, Yasunobu; Kagami, Shoji
Abstract: In this study, we describe an infant case of pulmonary atresia with intact ventricular septum associated with ventriculo-coronary arterial communication for which a modified Blalock–Taussig shunt operation was performed. He experienced repeated myocardial ischaemic attacks. Further examination revealed pulmonary sequestration in the right lower lobe. He therefore underwent a bidirectional Glenn operation and coil occlusion of the feeding arteries. His myocardial ischaemic attacks subsequently improved.